Relevant Outcomes in Pediatric Acute Respiratory Distress Syndrome Studies - Yehya, Nadir; Thomas, Neal J. (Frontiers in Pediatrics, 2016)
Despite distinct epidemiology and outcomes, pediatric acute respiratory distress syndrome (PARDS) is often managed based on evidence extrapolated from treatment of adults. The impact of non-pulmonary processes on mortality, as well as the lower mortality rate compared to adults with ARDS, renders the utilization of short-term mortality as a primary outcome measure for interventional studies problematic. However, data regarding alternatives to mortality are profoundly understudied, and proposed alternatives such as ventilator-free days may be themselves subject to hidden biases. Given the neuropsychiatric and functional impairment in adult survivors of ARDS, characterization of these morbidities in children with PARDS is of paramount importance. The purpose of this review is to frame these challenges in the context of the existing pediatric literature, and using adult ARDS as a guide, suggest potential clinically relevant outcomes deserving of further investigation. The goal is to identify important areas of study in order to better define clinical practice and facilitate future interventional trials in PARDS.